Vol 1. - "Swamy, N. Maheshwara" (Hyderabad, 2012)
This book contains a ready reckoner of case-laws, covering more than three decades of case law information in the context of other enactments reported in the prominent journals, like SCC, AIR, AIHC, ALT, ALD, CCC and CLR etc.Text of decision in the same words and same sense as split out by Hon'ble Judges in each cases.Table of provisions of the act of 1908 vis-a-vis the act of 1963.
Keywords: Civil Procedure and Courts